A Rapid UPLC Technique for Quantification of Tegafur, Oteracil and Gimeracil in Bulk and Pharmaceuticals and its Validation - Salva, Charumathi; Galla, Rajitha (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Tegafur (TEG) is a prodrug of 5-Fluorouracil (FU) that is mainly employed in the treatment of colorectal tumors combined with Gimeracil (GIM) and Oteracil (OTE) enhances its stability by enhancing the antineoplastic activity and reducing gastric irritation. Aim The key focus of this research was to design a rapid Ultra Performance Liquid Chromatography (UPLC) and validate that it is uncomplicated, exact, responsive and reliable for quantifying the concentrations of tegafur, oteracil and gimeracil in both their pure state and pharmaceutical formulations. Materials and Methods The UPLC method was developed using HSS C8 (100 mmx2.1 mm, 1.8 µm) column and the mobile phase was composed of phosphoric acid at a concentration of 0.1% v/v, with a pH of 2.0 and methanol in an 80:20 ratios. The process was carried out at a flow rate of 0.2 mL min-1, with injection volume of 5 µL and absorbance maxima of 282 nm. The technique was validated following the ICH standards. UPLC is a superior technique regarding performance thus it was chosen. Results and Discussion The elution time obtained was found to be below 2 min for all three drugs. The validated method’s linearity was determined to be between 40 and 240 µg/mL for tegafur, 31.6-189.6 µg/mL for oteracil and 11.6-69.6 µg/ mL for gimeracil. Tegafur, oteracil and gimeracil were found to have Detection Limit (LOD) and Quantitation Limit (LOQ) values of 0.3 μg/mL and 1 μg/mL, 0.2 μg/mL and 0.8 μg/mL, 0.1 μg/mL and 0.3 μg/mL, respectively. The developed method demonstrated high accuracy, as indicated by the RSD being less than 2%. Conclusion Thus, it can be employed as a method for evaluating stability and conducting regular quality control inspections for tegafur, gimeracil and oteracil.
Keywords: Tegafur; Gimeracil; UPLC; Oteracil; Stability